Perceived Organizational Perceived Organizational Support and Turnover Intention Mediated by Job Embeddedness - Novianty, Rina; Avianty , R. Rita; Fauziyyah, Nisrina Rifdah (Adpebi International Journal of Multidisciplinary Sciences, 2025)
The high level of turnover intention in various essential industries in Indonesia makes turnover intention an important issue and makes several companies develop strategies to retain the employees they have. This research aims to determine the effect of perceived organizational support on turnover intention mediated by job embeddedness in retail companies in Sumedang. The methods used in this research are descriptive and verification analysis. The data collection technique used questionnaires and interviews with 80 respondents. The data obtained was analyzed using the Partial Least Square (PLS) analysis technique using SmartPLS ver 3.2.7 for Windows. The research results show that the variable perceived organizational support hurts turnover intention. The variable perceived organizational support has a positive effect on job embeddedness. The job embeddedness variable hurts turnover intention. The results of this study also show that the job embeddedness variable mediates perceived organizational support on turnover intention.